Total synthesis of terpenes and their biological significance: A critical review - Aqsa Kanwal; Muhammad Bilal; Nasir Rasool; Muhammad Zubair; Syed Adnan Ali Shah; Zainul Amiruddin Zakaria (Multidisciplinary Digital Publishing Institute, 2022)
Terpenes are a group of natural products made up of molecules with the formula (C5H8 )n that are typically found in plants. They are widely employed in the medicinal, flavor, and fragrance industries. The total synthesis of terpenes as well as their origin and biological potential are discussed in this review.